2016
DOI: 10.21608/besps.2016.8646
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of t(14;18)(q32;q21) and BCL2 protein and their prognostic role in follicular lymphoma

Abstract: Background: Previous reports have suggested the significant association of t(14;18) (q32;q21) and follicular lymphoma (FL). However, little information is available in the literature on the relationship between BCL2 protein, BCL2 gene status in FL and the patient outcomes. Also, understanding of IGH/BCL2 molecular rearrangement using real time PCR (RT-PCR), in follicular lymphoma in relation to survival might provide a more accurate and rational method of risk stratification to guide treatment and might sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…BCL2 translocation was detected in 74% of all cases, which were 54.5% of FL cases and 20% DLBCL cases. A previous Egyptian study included fifty patients of FL showed that BCL-2 translocation was detected in 86% and 14% showed no translocation (19) . Also, BCL6 was positive in 58% of total cases, 45% and 13.6% of DLBCL and Follicular, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…BCL2 translocation was detected in 74% of all cases, which were 54.5% of FL cases and 20% DLBCL cases. A previous Egyptian study included fifty patients of FL showed that BCL-2 translocation was detected in 86% and 14% showed no translocation (19) . Also, BCL6 was positive in 58% of total cases, 45% and 13.6% of DLBCL and Follicular, respectively.…”
Section: Discussionmentioning
confidence: 96%